Do certain personality traits provide a mating market competitive advantage? Sex, offspring & the big 5. (1st March 2019) - Whyte, Stephen; Brooks, Robert C.; Chan, Ho Fai; Torgler, Benno
Abstract: This study uses the BIG 5 personality traits to quantitatively explore correlates of sexual frequency and reproductive success of a large sample ( N Male  = 2998; N Female  = 1480) of heterosexuals advertised to on an Australian dating website. Consistent with previous research we find that for both sexes, extraversion has a positive linear relationship with sexual frequency. The same is also observable for males that are more conscientious, more emotionally stable, and less agreeable; indicating that for men, a greater number of personality factors matter in explaining the variation in sexual activity. Higher extraversion or lower openness in males correlates with more offspring. Conversely, only more agreeable females have more offspring. Our non-parametric thin-plate spline analysis suggests certain combinations of the traits extraversion & agreeableness, extraversion & conscientiousness, and agreeableness & conscientiousness provide select males a mating market competitive advantage in relation to sexual frequency, compared to other males. Our findings suggest that greater variance in male traits and their particular combinations thereof may provide a fitness comparative advantage for males, but not necessarily for females.